A new species of Amaralia Fowler (Siluriformes: Aspredinidae) from the Paraná-Paraguay River Basin - Friel, John P.; Carvalho, Tiago P. (Zootaxa, 2016)
A new species of the banjo catfish genus Amaralia is described from the Paraná-Paraguay River Basin in central-western Brazil, Paraguay and northern Argentina. Amaralia oviraptor is distinguished from its single and allopatric congener, Amaralia hypsiura, by the greater number of dorsal-fin rays (3 vs. 2); by the absence of lateral contact between middle and posterior nuchal plates (vs. middle and posterior nuchal plates contacting each other laterally); and by a longer cleithral process (17.4–19.5 % of SL, mean 18.2 % vs. 14.0–17.2 % of SL, mean=15.5 %). Comments on the peculiar oophagic diet of Amaralia and an extended diagnosis of the genus are provided.